Up-front and Salvage Transoral Robotic Surgery for Head and Neck Cancer: A Belgian Multicenter Retrospective Case Series - Meulemans, Jeroen; Vanclooster, Christophe; Vauterin, Tom; D’heygere, Emmanuel; Nuyts, Sandra; Clement, Paul M.; Hermans, Robert; Delaere, Pierre; Vander Poorten, Vincent (Frontiers in Oncology, 2017)
Introduction/aim: We analysed the functional and oncologic outcomes of primary and salvage TORS procedures, performed in 3 Belgian institutions with a similar philosophy. Patients and methods: 86 patients who underwent TORS between 24-12-2009 and 25-09-2015 were retrospectively reviewed. Descriptive statistics, overall, disease specific and disease free survival (Kaplan-Meier), and the variation of these outcomes according to whether patients had primary or salvage TORS were evaluated (univariate log rank analysis). Results: Of 86 patients, 56 (65.1%) underwent TORS as a primary treatment and 30 (34.9%) as a salvage procedure for recurrent or second primary cancer. Tumor location was mainly oropharynx (N=63; 73.3%) followed by supraglottic larynx (N=11; 12.8%), hypopharynx (N=11; 12.8%) and larynx (N=1;1.2%). In the up-front TORS group, most tumors were classified as cT1 (N=23;41.1%)/pT1 (N=24;42.9%) or cT2 (N=27;48.2%)/pT2 (N=27;48.2%) and cN0 (N=18;32.1%), cN1 (N=13;23.2%) or cN2(N=25;44.6%). In the salvage TORS group, most tumors were cT1-rT1 (N=18;60.0%)/pT1-rpT1 (N=18;60.0%) or cT2-rT2 (N=12;40.0%)/pT2-rpT2 (N=7;23.3%) and cN0 (N=25;83.3%). Neck dissection was performed in 87.5% of primary cases and 30.0% of salvage cases. In the up-front TORS group, patients were postoperatively submitted to follow-up (N=13;23.2%) or received adjuvant radiotherapy, either as single modality (N=26;46.4%) or with concomitant cisplatin (N=15;26.8%). On the other hand, most salvage TORS patients did not receive any adjuvant therapy (N=19;63.3%). Mean and median follow-up was 23.1 and 21.2 months respectively. Functional results were excellent (no definitive tracheostomy, long term tube feeding in 1.8% of primary cases and 20% of salvage cases). In the up-front TORS group, estimated 2-year overall survival was 88.5% (SE=5.0%), 2-year disease specific survival was 91.8% (SE=4.6%) and 2-year disease free survival was 86.1% (SE=5.3%). In the salvage TORS group, estimated 2-year overall survival was 73.5% (SE=10.9%), 2-year disease specific survival was 93.3% (SE=6.4%) and 2-year disease free survival was 75.8% (SE=9.7%). Comparing outcome of primarily treated patients to salvage patients, a non-statistically significant trend towards better overall survival (p = 0.262) and disease free survival (p=0.139) was observed. Conclusion: This retrospective study confirms favorable oncologic and functional outcomes of TORS for selected head and neck malignancies, both in the primary and in the salvage setting.